English primary teacher agency in implementing teaching methods in response to language policy reform: a Vietnamese case study. Issue 1 (15th March 2021) - Le, Manh Duc; Nguyen, Hoa Thi Mai; Burns, Anne
ABSTRACT: Teacher agency has become a growing research interest in language education, especially at the critical juncture of widespread globalisation, when many nations including Vietnam, the context of the study, have promulgated a new language policy to respond to this transformation. However, teacher agency remains under-examined despite a small number of recent studies. In response to the paucity in the current LP literature, this qualitative case study, grounded in positioning theory, aims to explore how English teachers exercise their agency in response to the policy under prescribed contextual conditions. Data were collected from multiple sources including in-depth interviews, classroom observations, and documents. The findings showed that teachers were positioned (by the policy and their institutions) as 'mere' policy implementers who were expected to strictly follow the mandates and instructions transferred to them. Their implementation was regularly supervised and inspected by their stakeholders (including Department of Education and Training, Bureau of Education and Training, and school leaders). However, in the classroom context, the teachers attempted to adapt the policy mandates according to their interpretations, preferences, choices, and current teaching conditions. The study also proposes implications for policy makers, educational managers and school leaders to facilitate teachers' active roles in reform implementation.